Penggunaan Metode Think-Pair-Share Untuk Meningkatkan Kemampuan Penerapan Konsep Siswa Pada Topik Permutasi dan Kombinasi Kelas XI IPS 2 SMA YSKI Semarang [The Use of the Think-Pair-Share Method to Improve Grade 11 Students’ Capabilities in Applying Concepts of Permutation and Combination at YSKI Senior High School in Semarang] - Zai, Happy Putra Berkat; Dwikristanto, Yanuard P.; Yohansa, Meicheil (JOHME: Journal of Holistic Mathematics Education, 2017)
The ability to apply concepts requires students to use their knowledge or apply theory that has the same characteristics to solve problems in new concrete situations. According to the conducted observation, the researchers found a problem in applying the concept of probability in grade 11 students at YSKI High School, Semarang. The researchers believe that this particular problem needed to be resolved, so the researchers attempted to increase the student’s application of the concept through the Think-Pair-Share (TPS) method. This research was conducted from the 7th of August-24th of October 2016 with 24 students by using Kemmis & McTaggart's model of Classroom Action Research. The research was conducted in two cycles with each cycle being two meetings. The researchers used instruments that were validated for collecting the data. The instruments consisted of test sheets, student questionnaires, mentor and colleague observation forms, and journal reflections. An analysis of the data revealed that there was an increase in the application of the concept of the first cycle from 63% to 87% in the second cycle. To that end, researchers concluded that the use of TPS is able to increase student application of the concept in the topic of permutations and combinations in lessons on probability.ABSTRAK BAHASA INDONESIA: Kemampuan penerapan konsep menuntut siswa untuk menggunakan pengetahuan atau menerapkan teori yang memiliki ciri-ciri yang sama untuk memecahkan masalah dalam situasi yang baru atau konkret. Berdasarkan pengamatan yang dilakukan, peneliti menemukan masalah penerapan konsep materi peluang siswa SMA kelas XI IPS 2 YSKI Semarang. Peneliti merasa masalah tersebut penting untuk diselesaikan, sehingga peneliti berusaha untuk meningkatkan penerapan konsep siswa melalui penggunaan metode think-pair-share (TPS) dalam pembelajaran, serta mengetahui cara penggunaan metode TPS untuk meningkatkan kemampuan penerapan konsep siswa. Penelitian ini dilakukan mulai pada tanggal 7 Agustus 2016 – 24 Oktober 2016 terhadap 24 siswa dengan menggunakan metode Penelitian Tindakan Kelas model Kemmis dan Taggart. Penelitian Tindakan Kelas berlangsung dalam dua siklus dengan masing-masing siklus terdiri dari 2 pertemuan. Peneliti menggunakan instrumen yang telah divalidasi untuk mengumpulkan data. Instrumen yang digunakan terdiri dari lembar tes, lembar angket siswa, lembar observasi mentor dan teman sejawat dan jurnal refleksi. Dari hasil analisis dan pembahasan dapat dilihat peningkatan penerapan konsep dari siklus I 63% menjadi 87% di siklus II. Untuk itu, peneliti mengambil simpulan bahwa penggunaan metode TPS dapat meningkatkan penerapan konsep siswa materi peluang topik permutasi dan kombinasi.